EBV epitranscriptome reprogramming by METTL14 is critical for viral-associated tumorigenesis. - Fengchao Lang; Rajnish Kumar Singh; Yonggang Pei; Shengwei Zhang; Kunfeng Sun; Erle S Robertson (PLoS Pathogens, 2019)
Epstein-Barr virus (EBV) is a ubiquitous oncogenic virus that induces many cancers. N6-Methyladenosine (m6A) modification regulates many cellular processes. We explored the role of m6A in EBV gene regulation and associated cancers. We have comprehensively defined m6A modification of EBV latent and lytic transcripts. Furthermore, m6A modification demonstrated a functional role in regulation of the stability of viral transcripts. The methyltransferase METTL14 was induced at the transcript and protein levels, and knock-down of METTL14 led to decreased expression of latent EBV transcripts. METTL14 was also significantly induced in EBV-positive tumors, promoted growth of EBV-transformed cells and tumors in Xenograft animal models. Mechanistically, the viral-encoded latent oncoprotein EBNA3C activated transcription of METTL14, and directly interacted with METTL14 to promote its stability. This demonstrated that EBV hijacks METTL14 to drive EBV-mediated tumorigenesis. METTL14 is now a new target for development of therapeutics for treatment of EBV-associated cancers.